Validation of the Performance of A 10 Kg/Hour Potato Masher Using Solidworks-Based Simulation and Experimental Methods - Anggih Permata Putra; Septian Muhammad Wahid; Komarudin Komarudin (International Journal of Industrial Innovation and Mechanical Engineering, 2026)
Manual potato mashing is still limited in terms of efficiency and production capacity. This study aims to validate the performance of a 10 kg/h potato mashing machine using SolidWorks Simulation and experimental testing. The simulation analyzed the machine frame, main shaft, pestle pulley, and pestle using the parameters of von Mises stress, displacement, and factor of safety. The simulation results showed that all components experienced stress below the material yield strength, exhibited minimal deformation, and had a factor of safety greater than 1, indicating safe operating conditions. Experimental testing showed that the machine achieved an average production capacity of 9.39 kg/h, equivalent to 93.90% of the designed capacity, with an average processing time of 64 minutes and an average power consumption of 268.03 W, or 71.86% of the motor's rated power of 373 W (0.5 HP). Based on the simulation and experimental results, the potato mashing machine was confirmed to be safe, reliable, and capable of operating effectively in accordance with its design objectives.